2016
DOI: 10.1111/irv.12367
|View full text |Cite
|
Sign up to set email alerts
|

Trivalent and quadrivalent influenza vaccination effectiveness in Australia and South Africa: results from a modelling study

Abstract: BackgroundA modelling study was conducted to determine the effectiveness of trivalent (TIV) and quadrivalent (QIV) vaccination in South Africa and Australia.ObjectivesThis study aimed to determine the potential benefits of alternative vaccination strategies which may depend on community‐specific demographic and health characteristics.MethodsTwo influenza A and two influenza B strains were simulated using individual‐based simulation models representing specific communities in South Africa and Australia over 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
0
22
1
Order By: Relevance
“…Based on those that could be analyzed by HI, viruses isolated in Georgia and worldwide over the 2014-2017 seasons clearly differed antigenically from A/Texas/50/2012, while viruses in 3C.3a, 3C.2a and 3C.2a1 genetic groups appeared more closely related when assessed using post-infection ferret antisera raised against multiple representatives of each group. [37]. Genetic studies of the B/Victoria lineage viruses revealed several substitutions in the HA and NA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on those that could be analyzed by HI, viruses isolated in Georgia and worldwide over the 2014-2017 seasons clearly differed antigenically from A/Texas/50/2012, while viruses in 3C.3a, 3C.2a and 3C.2a1 genetic groups appeared more closely related when assessed using post-infection ferret antisera raised against multiple representatives of each group. [37]. Genetic studies of the B/Victoria lineage viruses revealed several substitutions in the HA and NA.…”
Section: Discussionmentioning
confidence: 99%
“…school, workplace, home, community) and determines each individual's infection status through time. [10][11][12]14 Simulation models create a "virtual world" of individuals whose daily movement, changing contact patterns and disease biology dynamics aim to replicate that of the real-world system in as much detail as data sources permit, such as data from the POLYMOD contact pattern study. 15 We modelled an Australian city, Newcastle in New South Wales.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, as influenza B rather tends to infect adolescents and young adults than elderly, the impact might be higher in LMICs which generally have younger populations. An individual-based modeling exercise found that QIV would reduce influenzarelated hospitalizations and deaths by 18% as compared with TIV in a community in South Africa between 2003 and 2013, while this was only 2% in Australia in the same period [68].…”
Section: Expert Commentarymentioning
confidence: 99%